(untitled) (Research, Society and Development, 2022)
This article aims to analyze educommunication in nursing education and its interlocution with information and communication technologies. It is a proposal for reflective analysis, with a qualitative approach, focusing on educommunication in nursing education contextualized in hybrid education through information and communication technologies, aiming at the autonomy of the student in the construction of knowledge. This article is built on the following topics of discussion: educommunication in nursing education; information and communication technologies and educommunication in the context of nursing and the educommunication dialogue for student education. In the case of nursing, with the advent of the Covid-19 Pandemic, the use of communication and information technologies became relevant in the academic environment, especially in remote education. Now with the gradual return of face-to-face activities, hybrid teaching has brought us a relevant perspective. And educommunication brings us important reflections on the contents taught in a dialogical perspective focused on student training and envisioning a transdisciplinary perspective both in teaching and in health care. Therefore, educommunication provide us with relevant proposals for teaching based on dialogue in which the student is the center of the teaching and learning process.